DEAR READER - Petrek, Prof. Josef (Biomedical papers, 2006)
Sixty years ago on the 21st February 1946, the University of Palacky in Olomouc was re-established as an educational institution for students of theology, medicine and philosophy. 'Biomedical Papers', formerly 'Acta Universitatis Palackianae Olomucensis Facultatis Medicae', a specialist periodical of the Faculty of Medicine, also celebrates this year since its 150th volume is coming out in 2006....
Keywords: Biomedical Papers; Acta Universitatis Palackianae Olomucensis Facultatis Medicae